INDONESIA'S FOREIGN DEBT DEVELOPMENT AND MACROECONOMIC VARIABLES - Malini, Helma; Seinna, Yufita Efie; Rustam, Rustam (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
Indonesia's foreign debt presents a dilemma for the government because, on the one hand, repayment of maturing loans has become a burden in the government budget as an expense item that must be considered. Loans, on the other hand, are a source of government revenue that can be used to close the budget deficit. Economic variables are the focus of this research. The type of research is associative descriptive research, with secondary data acquired from relevant institutions and agencies from 208 to 2020 and evaluated using descriptive and time series analysis. The results showed that the Rupiah exchange rate had a significant effect on the development of Indonesia's foreign debt. This conclusion implies that the government must stabilize the rupiah exchange rate against the US dollar in order to avoid the debt burden and interest payments being incurred and the occurrence of an economic crisis in the future. The public should utilize the government's jobless relief program. The higher the level of tax compliance from taxpayers, the higher state revenues and the ability to pay debts.